Cabbage Palm Caterpillar, Litoprosopus futilis (G. & R.) (Insecta: Lepidoptera: Noctuidae: Ophiderinae) - Geo Wallace Dekle (EDIS)
This document is EENY-095 (originally published as DPI Entomology Circular No. 75), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 1999.